Defining Factors behind the Financial Sustainability of Microfinance Institutions (MFIs) of Bangladesh - Yasmin, Farhana; Sumi, Mst. Sharmin Sultana; Rabeta, Maliha; Ima, Ummay Mahima (International Journal of Economics and Financial Issues, 2024)
Bangladesh can be proudly recognized as the pioneer of the microcredit concept. This paper aims to discover the potential firm-specific factors that influence the economic stability of MFIs (microfinance institutions) in Bangladesh. The study has collected quantitative data on one sustainability variable and six predictor variables through performance analysis of the top 120 MFIs of Bangladesh from 2022 to 2023. MFIs having 110% or more operational sustainability have been regarded as financially sustainable and examined based on managerial inefficiency, MFIs size, leverage, breadth of outreach, loan intensity, and deposit mobilization. The findings revealed that except deposit mobilization, all other stated predictors have imposed statistically significant effects on the financial sustainability of the microfinance institutions of Bangladesh of which size and loan intensity have a positive impact whereas managerial inefficiency, leverage, and breadth of outreach have a negative impact. The results of the research can be utilized to increase knowledge about the factors that can be eliminated or controlled to achieve financial sustainability and eventually, all the MFIs being operated in society, especially those who are facing challenges in accumulating their funds will benefit from this research by getting an idea of which determinants to control.